Diagnosing multiple short circuit switches faults in wind turbine doubly-fed induction generator - Sara Kharoubi; Lamiaa El Menzhi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In the current paper, the inverter feeding doubly fed induction generator (DFIG) in the case of short circuit switches fault is presented. Defects diagnosis is based on the so-called the Lissajous curves of DFIG rotor currents. For this purpose, the modeling of the variable speed wind energy conversion chain based on the DFIG, is firstly introduced, after that a description of the voltage source inverter operating mode is presented. Finally, rotor currents Lissajous curves are analyzed in case of a non-defective and defective inverter. Simulation results were achieved using MATLAB^®- SIMULINK^® package, thus confirming the efficiency of the proposed method.